Impacts of α-tocopherol (vitamin E) and L-ascorbic acid (vitamin C) on reproductive performance in female yellow mystus (Hemibagrus spilopterus) - Somnuek, Natthawan; Kasamawut, Krittima; Somnuek, Talerngkiat; Ngamsnae, Praneet; Sreeputhorn, Kosit; Saowakoon, Samnao (Agriculture and Natural Resources, 2025)
Importance of the work: The success of breeding in fish is influenced by egg quality, which can be enhanced through vitamin supplementation in the diet. Objectives: To evaluate the effects of vitamins C and E, both individually and in combination, on the growth, reproductive performance and sex hormone levels in female yellow mystus. Materials and Methods: Female yellow mystus aged 1 yr were fed a commercial diet with 32% protein, supplemented with: 1) no vitamins (the control); 2) vitamin C at 1,000 mg/kg; 3) vitamin E at 500 mg/kg; or 4) a combination of 1,000 mg/kg vitamin C + 500 mg/kg vitamin E. Data were collected on growth, ovary weight, gonadosomatic index (GSI), fecundity and hormone levels after 30 d and 60 d of treatment, while the fertilization rate and the hatching rate were evaluated only at 60 d. Results: There were synergistic effects from adding vitamin C and E. Fish fed the combined vitamin supplementation showed improved GSI, ovary weight, estrogen and progesterone levels. Vitamin C supplementation alone (at 30 d) also increased fecundity. By day 60, all vitamin-supplemented groups showed improved fecundity, fertilization and hatching rates. Main finding: The combination of vitamin C and vitamin E significantly improved reproductive parameters in yellow mystus, consisting of fecundity, fertilization rates, hatching rates and sex hormones, offering potential for enhanced fry production.